GE_GERICHTE A/712/2022 vom 3. März 2022 - GE Cour de justice (2022)
DÉTENTION AUX FINS D'EXPULSION;MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);PROCÉDURE ÉCRITE | Trafic de drogue | LEI.75.al1.letg; LEI.76.al1.letb